1996
DOI: 10.1021/ma951058e
|View full text |Cite
|
Sign up to set email alerts
|

EXAFS Studies of Various Sulfonated and Carboxylated Cadmium Ionomers

Abstract: Four sulfonate ionomers and one carboxylate ionomer, all neutralized with cadmium, were studied using the technique of extended X-ray absorption fine structure (EXAFS) spectroscopy. The cadmium in all four sulfonate ionomers had essentially identical EXAFS oscillations, which suggests that the influence of the identity of the polymer matrix on the local aggregate structure is minimal. In contrast, the cadmium in the carboxylate ionomer had a substantially different local environment, showing that, as expected,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…[N 1444 + ] vs. [N 1222 + ], that will decrease the association between ion pairs (which lead to ionic cross-links between polymer segments) and by the additional plasticiser effect of these larger cations. 23,32,33 It is also noted that the ionomer with higher EA content, e.g. N 1222 (a), shows a lower T g , which is because the exible acrylate domain will lower the T g , as observed in Na[PSTFSI-co-EA] in our previous study.…”
Section: Raman Spectroscopymentioning
confidence: 64%
“…[N 1444 + ] vs. [N 1222 + ], that will decrease the association between ion pairs (which lead to ionic cross-links between polymer segments) and by the additional plasticiser effect of these larger cations. 23,32,33 It is also noted that the ionomer with higher EA content, e.g. N 1222 (a), shows a lower T g , which is because the exible acrylate domain will lower the T g , as observed in Na[PSTFSI-co-EA] in our previous study.…”
Section: Raman Spectroscopymentioning
confidence: 64%
“…[30][31][32] Tudyryn et al reported that, 31 with constant ion content, their polyester-sulfonate ionomers showed T g decreasing as counterion size increases. They suggest that this is caused by two factors 32,33 (i) larger counterions associate less with the backbone anions, forming fewer and weaker physical cross-links that then leads to a decrease in T g for ionomers (ii) larger counterions act as plasticizers, further lowering T g . However, N 14,111 + possesses the highest T g , among the ionomers prepared in this work, despite having the longest aliphatic chain.…”
Section: Resultsmentioning
confidence: 99%
“…Polystyrene was sulfonated using the method of Lundberg et al 14 Details of the sulfonation method are given in a previous publication. 15 The 3.4 and 5.7 mol % sulfonate substitution levels were synthesized. The acid form was dissolved in a 90/10 v/v mixture of toluene/methanol and neutralized with a stoichiometric amount of zinc acetate dihydrate to produce fully neutralized zinc sulfonated polystyrene.…”
Section: Methodsmentioning
confidence: 99%